Perencanaan dan Analisis Biaya Investasi antara Perkerasan Kaku dengan Perkerasan Lentur pada Jalur Trans Jakarta Busway: Studi Kasus pada Trans Jakarta Busway Koridor 8 antara Halte Pondok Indah 2 hingga Halte Permata Hijau - Prahara, Eduardi; Sunarsa, Andika (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Types of rigid pavement for road has been widely used in Indonesia, ranging from toll roads to the outer town road. Rigid pavement is considered more powerful than the flexible pavement. In other words, rigid pavement is expected to have a longer service life and minimal maintenance. The construction cost for rigid pavement is more expensive compared to flexible pavement. While the need for rigid pavement maintenance is cheaper than for flexible pavement. Seen from investment point of view, rigid pavement is more profitable than flexible pavement, because the annual fee required for rigid pavement is less. Due to the comparations, an analysis is performed in this study to select which type of pavement is best used in the future.